Catalytic Aerobic Photo‐oxidation of a Methyl Group on a Heterocycle to Produce an Aldehyde via Homolytic CI Bond Cleavage caused by Irradiation with Visible Light. Issue 2 (12th January 2016) - Nagasawa, Y.; Tachikawa, Y.; Yamaguchi, E.; Tada, N.; Miura, T.; Itoh, A.
Abstract: A new catalytic method was developed for photo‐oxidizing the methyl group on aromatic heterocycles such as benzothiazole, benzoxazole, and quinoline to produce the corresponding aldehyde. This is the first report of the metal‐free catalytic synthesis of benzothiazole‐2‐carboxaldehydes using molecular oxygen as the terminal oxidant. Abstract :